Temporary extra jobs for immigrants: Merging lane to employment or dead-end road in welfare? - Stephan L. Thomsen; Thomas Walter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
We evaluate the effects of the most frequently used German welfare-to-work program on the employment chances of immigrant welfare recipients. In particular, we investigate whether program effects differ between immigrants and natives and what might cause these potential differences. Our results reveal that the program fails to achieve its objectives. The effects are more adverse for natives, but the program does not help otherwise identical immigrants to leave the welfare system either. Therefore, the program is a dead-end road rather than a merging lane to regular employment both for natives and for immigrants.
Keywords: I38; C14; J61; 330; Immigrants; employment programs; evaluation; decomposition of effects; Germany; Aktivierende Sozialhilfe; Leiharbeit; Arbeitsmarktpolitik; Wirkungsanalyse; Migranten; Sozialhilfeempfänger; Berufliche Integration; Deutschland